Telegram - Hastings, Cristina Casati Stampa di Soncino, Viscountess, 1901-1953
010-0101-001 POST OFFICE TELEGRAM Prefix. Time handed in. Office of Origin and Service Instructions. Words. 48 148 12.7 LONDON T 68 Sir Walter Citrine Trade Union Congress Plymouth = Just received following telegram from Viscount Churchill in Barcelona quote returned from front advise widest publicity be given following facts myself saw bodies women children killed by bombs identified as German dropped from Trimotor German plane constant proofs Italians Germans steadily supplying rebels armaments and services unquote would be so grateful if you would communicate this information to Congress = Viscountess Hastings + + 292/946/10/109